Metode Penulisan Usul Fikih (Kajian Komparatif terhadap Tiga Aliran dalam Usul Fikih) - Trigiyatno, Ali (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
This text compares among three methods in Usul al-Fiqh: Hanafiyah, Shafi'iyah, and tariqah al-jami'. Hanafiyah has some strengths such as rich of examples in furu', close with the reality and concise in discussion. The weakness of this method is it causes a kind of fantastic and rich of argumentation. Shafi'iyah method is too narrow in philosophical point of view and lack for examples. Tariqah al-jami' generally could overcome the weakness of those two methods above.